Nucleomorph Genome Sequence of the Cryptophyte Alga Chroomonas mesostigmatica CCMP1168 Reveals Lineage-Specific Gene Loss and Genome Complexity - Moore, Christa E. (Oxford University Press, 2012)
Cryptophytes are a diverse lineage of marine and freshwater, photosynthetic and secondarily nonphotosynthetic algae that acquired their plastids (chloroplasts) by “secondary” (i.e., eukaryote–eukaryote) endosymbiosis. Consequently, they are among the most genetically complex cells known and have four genomes: a mitochondrial, plastid, “master” nuclear, and residual nuclear genome of secondary endosymbiotic origin, the so-called “nucleomorph” genome. Sequenced nucleomorph genomes are ∼1,000-kilobase pairs (Kbp) or less in size and are comprised of three linear, compositionally biased chromosomes. Although most functionally annotated nucleomorph genes encode proteins involved in core eukaryotic processes, up to 40% of the genes in these genomes remain unidentifiable. To gain insight into the function and evolutionary fate of nucleomorph genomes, we used 454 and Illumina technologies to completely sequence the nucleomorph genome of the cryptophyte Chroomonas mesostigmatica CCMP1168. At 702.9 Kbp in size, the C. mesostigmatica nucleomorph genome is the largest and the most complex nucleomorph genome sequenced to date. Our comparative analyses reveal the existence of a highly conserved core set of genes required for maintenance of the cryptophyte nucleomorph and plastid, as well as examples of lineage-specific gene loss resulting in differential loss of typical eukaryotic functions, e.g., proteasome-mediated protein degradation, in the four cryptophyte lineages examined.